On the robustness of minimum wage effects: Geographically-disparate trends and job growth equations - John T. Addison; McKinley L. Blackburn; Chad D. Cotti (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2014)
Recent attempts to incorporate spatial heterogeneity in minimum-wage employment models have been attacked for using overly simplistic trend controls, and for neglecting the potential impact on employment growth. We investigate whether such considerations call into question our earlier findings of statistically insignificant employment effects for the restaurant-and-bar sector. We find that a focus on employment levels is still appropriate, and nonlinear trend controls do not dislodge our limited support for the existence of minimum-wage effects.
Keywords: J23; J38; 330; minimum wages; employment; employment change; spatial controls